Longitudinal Study of Caries Development from Childhood to Adolescence. (July 2017) - Hall-Scullin, E.; Whitehead, H.; Milsom, K.; Tickle, M.; Su, T.-L.; Walsh, T.
The World Health Organization (WHO) stated that globally, dental caries is the most important oral condition. To develop effective prevention strategies requires an understanding of how this condition develops and progresses over time, but there are few longitudinal studies of caries onset and progression in children. The aim of the study was to establish the pattern of caries development from childhood into adolescence and to explore the role of potential risk factors (age, sex, ethnicity, and social deprivation). Of particular interest was the disease trajectory of dentinal caries in the permanent teeth in groups defined by the presence or absence of dentinal caries in the primary teeth. Intraoral examinations to assess oral health were performed at 4 time points by trained and calibrated dentist examiners using a standardized, national diagnostic protocol. Clinical data were available from 6, 651 children. Mean caries prevalence (% D3 MFT > 0) was 16.7% at the first clinical examination (ages 7–9 y), increasing to 31.0%, 42.2%, and 45.7% at subsequent examinations. A population-averaged model (generalized estimating equations) was used to model the longitudinal data. Estimated mean values indicated a rising D3 MFT count as pupils aged (consistent with new teeth emerging), which was significantly higher (4.49 times; 95% confidence interval, 3.90–5.16) in those pupils with caries in their primary dentition than in those without. This study is one of the few large longitudinal studies to report the development of dental caries from childhood into adolescence. Children who developed caries in their primary dentition had a very different caries trajectory in their permanent dentition compared to their caries-free contemporaries. In light of these results, caries-free and caries-active children should be considered as 2 separate populations, suggesting different prevention strategies are required to address their different risk profiles.